INSTITUTIONAL SUPPORT AND ENTREPRENEURIAL LEARNING IN MSMES: A FRAMEWORK FOR SUSTAINABLE LOCAL BUSINESS DEVELOPMENT - Nida Garnida Fitrianti; Lili Adi Wibowo (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for institutional support and entrepreneurial learning in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, it explains how institutional accessibility, entrepreneurial learning, network brokerage, capability building, and sustainable local business development can be organized into practical managerial routines. The manuscript does not claim primary survey, interview, experimental, or statistical data. It proposes a staged cycle of diagnosis, capability configuration, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention. The framework emphasizes proportionate implementation and identifies implications for owner-managers, ecosystem institutions, and future empirical research.